Effectiveness of Innovative Ergonomic Models in Preventing Occupational Fatigue in Rice Farmers - Aswin, Budi; Rini, Willia Novita Eka; Hidayati, Fajrina (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Ergonomic work hazards are potential hazards that can negatively affect the health of farmers. One of the ergonomic hazards that farmers often experience is fatigue. This study aims to analyze the effectiveness of innovative ergonomic models and the preparation of balanced calorie needs in preventing work fatigue in rice farmers. Methods: The type of research used is a randomized controlled trial (RCT) design, which is the most powerful design to evaluate the intervention used, namely the effectiveness of innovative ergonomic models and the preparation of balanced calorie needs in preventing occupational fatigue in rice farmers. The population in this study were all farmers in Pudak Village, Kumpeh Ulu Subdistrict, Muaro Jambi Regency, totaling 238 people. The number of research samples was 68 farmers has taken using simple random sampling technique. Data were analyzed to determine the effectiveness of innovative ergonomic models using the ANOVA test with (α = 0.05). Result: There was a difference in the effectiveness of innovative ergonomic models in preventing work fatigue between at least two groups of rice farmers. Conclusion: the provision of stretching and snacks coupled with rest periods is most effective in preventing occupational fatigue. As for occupational fatigue, the provision of stretching, snacks, and rest time and the provision of simple education on the hazards of work ergonomics are effective in preventing occupational fatigue in rice farmers.